On-Chip Low-Power Gray Code Generation Based on Opto-Mechanical Microring Resonators - Li Liu; Yue Yang; Jin Yue; Shasha Liao (IEEE Photonics Journal)
We propose and experimentally demonstrate on-chip energy-efficient Gray code generation based on a scalable and compact optical encoder. The operation principle of the integrated encoder is based on the nonlinear effects in silicon opto-mechanical microring resonators (MRRs), which could be excited by ultra-low input powers. By adjusting the input powers with hierarchical power levels, the red-shifts of the MRR transmission spectrum could be flexibly manipulated. In this case, the output powers of the MRR drop-port and through-port could be controllable and switchable to generate different codes. Through tuning the optical encoding powers in a specific rule, 4-bit and 2-bit Gray codes have been successfully demonstrated. The required power of the proposed 4-bit encoder is as low as −6 dBm, which is favorable to build energy-efficient optical encoding systems. To the best of our knowledge, we have realized a nano-mechanical optical encoder with the lowest required power. Moreover, the encoder structure has great scalability, thus 2N-bit Gray code could be generated by utilizing 2N-1 add-drop MRRs. With the dominant advantages of ultra-low power consumption (−6 dBm), compact size (0.08 mm2) and great scalability, the proposed optical encoder has many significant applications in optical encoding and communication chips.